The prognostic value of vasoresponse to nitric oxide in patients with chronic thromboembolic pulmonary hypertension. (3rd October 2022) - Uphus, J; Hu, J R; Huang, S; Panzenboeck, A; Sadushi-Kolici, R; Shafran, I; Skoro-Sajer, N; Gerges, C; Brittain, E; Lang, I M
Abstract: Background: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterized by pulmonary artery obstructions due to organized chronic thrombotic material in major pulmonary arteries. In addition, about half of the patients suffer from a small vessel pulmonary arteriopathy that is a strong predictor of outcomes. Currently available treatment of CTEPH includes interventional strategies such as pulmonary endarterectomy (PEA) and balloon pulmonary angioplasty (BPA), and non-interventional strategies with PH-specific medications. A simple way of assessing small vessel disease is the degree of vasodilation ("vasoresponse") in response to inhaled nitric oxide (iNO). In idiopathic pulmonary arterial hypertension vasoresponse serves as the best marker for good prognosis and treatment selection. In CTEPH, the prognostic value of vasoresponse remains unclear. Purpose: We investigated the prognostic value of three definitions of vasoresponse to nitric oxide in patients with CTEPH. Methods: We studied 325 CTEPH patients who underwent baseline diagnostic right heart catheterization (RHC) with 40ppm iNO testing at a general hospital (AKH) between 1995 and 2019. Cox regression models, adjusting for covariates including age, sex, comorbidities, and markers for disease severity at baseline, such as proBNP, GFR, NYHA functional class, were used to determine the risk of death or lung transplantation with respect to vasoresponse. We analysed three currently used definitions of vasoresponse to nitric oxide – the classical definition (CD) as a 10mmHg reduction in mPAP to a level below 40mmHg; an absolute definition (AD) as a 10mmHg reduction in mPAP regardless of resulting mPAP; and the percent definition (PD) as a 10% reduction in mPAP regardless of resulting mPAP. Results: Patients had a median age of 62 (interquartile range [IQR]: 50, 71) at time of baseline right heart catheterization and 50% were female. During a median observation time of 5 years (IQR: 2.2, 9.0), the combined endpoint of death or lung transplantation occurred in 88 cases (27%). In the cox regression model PD vasoresponders, showed improved survival when undergoing PEA (p=0.0019). In PD vasoresponsive patients who were not given PEA surgery (n=66), PH medication therapy was associated with improved survival (p=0.0053), whereas BPA had no association with survival (p=0.58). In PD non-vasoresponsive patients who were not given PEA surgery (n=107) BPA improved survival (p<0.0001), whereas PH medication therapy did not improve survival (p=0.08). Conclusion: The PD vasoresponse to iNO carries valuable prognostic information about freedom from death or lung transplantation in patients with CTEPH. In patients who are not eligible for PEA, PD vasoresponse can improve optimal therapy selection. Funding Acknowledgement: Type of funding sources: None.